The Exploring of Chinese Window Lattice Patterns in Ceramic Decoration: A Case Study in Suzhou Gardens - Anjing, Zhuo; Sirivesmas , Veerawat; Punyalikit, Ruenglada (Journal of Roi Kaensarn Academi, 2024)
This paper takes the visual analysis of window lattice patterns as the starting point and proposes a design application method for window lattice patterns in contemporary ceramic decorative art. This study has three objectives: 1. To conduct a systematic study on the patterns of Chinese window lattices; 2. Explore design methods for window lattice patterns; 3. Develop the application of window lattice patterns in ceramic decorative art by combining contemporary ceramic art creation concepts. The first is a literature review and fieldwork in Suzhou will be conducted, summarize the window lattice evolution rules. Subsequently, based on experimental methods, a detailed analysis of ceramic glazing, shaping, and firing techniques will be carried out. This will support creative practices to explore various ways in which window lattice patterns can be represented in ceramics. Gradually breaking away from traditional approaches while incorporating them into the essence of the designs, these patterns will be applied to new design developments. The researcher’s focus on exploring the development forms of window lattice patterns and their hidden philosophical meanings, expanding different modes of expression in ceramic decoration, and created a new visual language. Through the study and exploration of window lattice patterns, it is hoped that this will deepen people’s understanding and development of traditional Chinese culture, inspire designers engaged in ceramic art, and provide certain theoretical references.